Enhancing Mathematical Representation Skills through the Traditional Game Ceprek Lombok - Ananda, Sustia; Pardi, M. Habib Husnial; Kusaeri, Al (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2025)
Mathematical representation skills play a crucial role in learning mathematics, particularly in connecting mathematical concepts into symbols and diagrams, especially in the context of plane geometry. This study investigates the improvement of students’ mathematical representation skills through the use of the traditional game Ceprak Lombok. A quantitative approach with a quasi-experimental design was employed. The population consisted of all seventh-grade students (N = 158), with a sample of 35 students from class VII B. Data were collected using pretest and posttest instruments to measure students’ mathematical representation skills, supported by observation sheets to monitor the intervention process. Data analysis was performed using SPSS, including normality and homogeneity tests as prerequisites, followed by hypothesis testing. The results showed that the data were normally distributed (p > 0.05) and homogeneous (p > 0.05). Hypothesis testing further revealed a significant improvement in students’ learning outcomes after the treatment (p < 0.05). These findings suggest that the Ceprak Lombok traditional game is effective in enhancing mathematical representation skills and provide practical implications for teachers to utilize traditional games as engaging and effective strategies for developing students’ mathematical competencies.